The Influence Of Corporate Culture, Leadership Style, Work Environment, And Work Discipline On Employee Performance (Case Study At PT. PLN (Persero) UPP JBTB 3) - Bustanul Arifin; Kuswandi, Kuswandi; Sri Rahayu (Jurnal Ekonomi, 2024)
This study aims to analyze the simultaneous influence of corporate culture, leadership style, work environment, and work discipline on employee performance at PT. PLN (Persero) UPP JBTB 3. Based on the F-test results, the variables of corporate culture, leadership style, work environment, and work discipline significantly affect employee performance both partially and simultaneously. This research employs a quantitative approach with a survey method by distributing questionnaires to 43 employees working at PT. PLN (Persero) UPP JBTB 3. The collected data were analyzed using multiple linear regression. The analysis results indicate that corporate culture, leadership style, work environment, and work discipline significantly influence employee performance. These findings suggest that to enhance employee performance, the company must pay serious attention to these four variables. The study recommends that the company strengthen its corporate culture, implement effective leadership styles, create a conducive work environment, and enforce good work discipline.